Pseudomonas aeruginosa exoenzymes U and Y induce a transmissible endothelial proteinopathy - Morrow, K. Adam (Am J Physiol Lung Cell Mol Physiol, 2015)
We tested the hypothesis that Pseudomonas aeruginosa type 3 secretion system effectors exoenzymes Y and U (ExoY and ExoU) induce release of a high-molecular-weight endothelial tau, causing transmissible cell injury characteristic of an infectious proteinopathy. Both the bacterial delivery of ExoY and ExoU and the conditional expression of an activity-attenuated ExoU induced time-dependent pulmonary microvascular endothelial cell gap formation that was paralleled by the loss of intracellular tau and the concomitant appearance of high-molecular-weight extracellular tau. Transfer of the high-molecular-weight tau in filtered supernatant to naïve endothelial cells resulted in intracellular accumulation of tau clusters, which was accompanied by cell injury, interendothelial gap formation, decreased endothelial network stability in Matrigel, and increased lung permeability. Tau oligomer monoclonal antibodies captured monomeric tau from filtered supernatant but did not retrieve higher-molecular-weight endothelial tau and did not rescue the injurious effects of tau. Enrichment and transfer of high-molecular-weight tau to naïve cells was sufficient to cause injury. Thus we provide the first evidence for a pathophysiological stimulus that induces release and transmissibility of high-molecular-weight endothelial tau characteristic of an endothelial proteinopathy.